2017
DOI: 10.11604/pamj.2017.28.74.13418
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs de Risque du Décollement de Rétine au Togo

Abstract: Introductionle décollement de rétine pose un problème de prise en charge dans les pays en développement par manque de plateau technique. Sa prévention passe par la connaissance et l'éviction de ses facteurs de risque. Le but de l'étude était d'identifier les facteurs de risque du décollement de rétine chez le Togolais. Méthode: il s'est agi d'une étude rétrospective et descriptive, réalisée dans le service d'ophtalmologie du Chu-Campus et dans un cabinet privé d'ophtalmologie de Lomé du 2 Janvier 2011 à 31 Déc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This means that the true prevalence is unknown and there is a potential public health problem. A study from Togo revealed that Sickle cell disease is the cause of 16% of retinal detachments [22]. They concluded that sickle cell disease is a significant major risk factor(p=0.0003) for tractional retinal detachment, a type of retinal detachment that can be surgically challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the true prevalence is unknown and there is a potential public health problem. A study from Togo revealed that Sickle cell disease is the cause of 16% of retinal detachments [22]. They concluded that sickle cell disease is a significant major risk factor(p=0.0003) for tractional retinal detachment, a type of retinal detachment that can be surgically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that sickle cell disease is a significant major risk factor(p=0.0003) for tractional retinal detachment, a type of retinal detachment that can be surgically challenging. [22]. Sickle Cell retinopathy can cause severe eye disease resulting in visual loss, and patients must be educated and encouraged to get early screening [23] .…”
Section: Discussionmentioning
confidence: 99%
“…The use of vitrectomy in Sub-Saharan Africa has been limited due to low resources and lack of skilled manpower [116]. Maneh et al looked at the risk factors for retinal detachments in Togo and found that patients with SCD accounted for 16% of cases that presented with retinal detachments [117].…”
Section: Improving Surgical Outcomesmentioning
confidence: 99%